2013
DOI: 10.7566/jpsjs.82sa.sa003
|View full text |Cite
|
Sign up to set email alerts
|

QENS Study of Diffusive and Localized Cation Motions of Pyridinium-Based Ionic Liquids

Abstract: We have investigated stochastic motions of the cations of the pyridinium based ILs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…It is particularly suitable to obtain information about the geometrical and dynamical features of diffusion processes in hydrogenated systems. Some recent QENS studies on pyridinium based ionic liquids have revealed two independent relaxation processes in the system 38,39 . Similarly, different mobilities of different molecules in glyceline DES (glycerol+choline chloride) was also observed using QENS experiments 40 .…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly suitable to obtain information about the geometrical and dynamical features of diffusion processes in hydrogenated systems. Some recent QENS studies on pyridinium based ionic liquids have revealed two independent relaxation processes in the system 38,39 . Similarly, different mobilities of different molecules in glyceline DES (glycerol+choline chloride) was also observed using QENS experiments 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, also the associated activation energies underlie such an averaging. While the translational diffusion of the ionic liquid in the pores of MoC-15 has an activation energy similar to the bulk value of 12.3-14.8 kJ/mol [37,38,40,41], the one for BC-6-no is higher, whereas it is smaller for BC-6. It is imaginable that the interaction with the pore wall and structural changes of the ionic liquid that are provoked by the respective pore morphology lead to an alteration of the ionic liquid's dynamics and the related activation energies.…”
Section: B Full Quasielastic Spectramentioning
confidence: 85%
“…Subsequently the nanopores of the carbide-derived carbons are filled with the room-temperature ionic liquid 1-Nbutylpyridinium bis-[(trifluoromethyl)sulfonyl]imide, in the following shortly denoted as [BuPy][Tf 2 N] and whose bulk molecular dynamics have been already extensively studied [37][38][39][40][41]. The structure formulas of the cation and anion are depicted in Fig.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently the nanopores of the carbide-derived carbons are filled with a room-temperature ionic liquid 1-Nbutylpyridinium bis-((trifluoromethyl)sulfonyl)imide, in the following shortly denoted as [BuPy][Tf 2 N] and whose bulk molecular dynamics have been already extensively studied. [37][38][39][40][41] The structure formulas of the cation and anion are depicted in Fig. 2.…”
Section: Sample Preparation and Characterisationmentioning
confidence: 99%